2000
DOI: 10.1091/mbc.11.10.3277
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetes Autoantigen ICA69 and ItsCaenorhabditis elegansHomologue,ric-19, Are Conserved Regulators of Neuroendocrine Secretion

Abstract: ICA69 is a diabetes autoantigen with no homologue of known function. Given that most diabetes autoantigens are associated with neuroendocrine secretory vesicles, we sought to determine if this is also the case for ICA69 and whether this protein participates in the process of neuroendocrine secretion. Western blot analysis of ICA69 tissue distribution in the mouse revealed a correlation between expression levels and secretory activity, with the highest expression levels in brain, pancreas, and stomach mucosa. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 57 publications
0
38
0
1
Order By: Relevance
“…The cellular function of ICA69 is not clear. It has been suggested that ICA69 might be involved in neuron-endocrine secretion, as the mutation of ric-19, the Caenorhabditis elegans homolog of ICA69, leads to resistance to inhibitors of acetylcholinesterase, a phenomenon attributed to defective acetylcholine release (Pilon et al, 2000). ICA69 was found to be located around the Golgi and nearby vesicles (Spitzenberger et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular function of ICA69 is not clear. It has been suggested that ICA69 might be involved in neuron-endocrine secretion, as the mutation of ric-19, the Caenorhabditis elegans homolog of ICA69, leads to resistance to inhibitors of acetylcholinesterase, a phenomenon attributed to defective acetylcholine release (Pilon et al, 2000). ICA69 was found to be located around the Golgi and nearby vesicles (Spitzenberger et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…ICA69 colocalizes with PICK1 except at synapses ICA69 was initially identified from pancreatic ␤ cells and subsequently found to be expressed in many other tissues, including the brain (Pietropaolo et al, 1993;Pilon et al, 2000). PICK1 is known to be highly expressed in the brain, but its expression in the pancreas has not been examined (Xia et al, 1999).…”
Section: Ica69 and Pick1 Form Tight Complexes In Vitro And In Vivomentioning
confidence: 99%
“…They project in opposite directions, differ in their circumferential trajectories (NSM projects in the pharyngeal nerve ring while M2 projects anterior through it, piercing a path through he pm4 cell), and NSM but not M2 is branched. They also offer relatively simple shapes that facilitate scoring of deviant forms, and, importantly, useful green fluorescent protein (GFP) reporters are available for their visualization: pRIC-19::GFP for the M2 neurons (Pilon et al, 2000), and pTPH-1::GFP for the NSM neurons (Sze et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Originally identified by immunoscreening of an islet cDNA expression library with prediabetic sera, islet cell autoantigen of 69 kDa (ICA69) 1 is an evolutionary conserved gene with homologues in the nonmammalian model organisms Drosophila melanogaster and Caenorhabditis elegans (1)(2)(3). Like most antigens of type 1 diabetes, ICA69 is enriched in pancreatic ␤-cells and neurons (4).…”
mentioning
confidence: 99%
“…Although ICA69 deficiency in mice does not induce any obvious phenotype, the knockout of its C. elegans homologue compromises neurotransmission (3,6). This finding has led to the hypothesis that ICA69, despite lacking membrane anchoring signals, is linked to neuronal synaptic vesicles (SVs) and the related synaptic-like microvesicles (SLMVs) of endocrine cells (3).…”
mentioning
confidence: 99%